2016
DOI: 10.1002/admi.201600725
|View full text |Cite
|
Sign up to set email alerts
|

The PLA/ZIF‐8 Nanocomposite Membranes: The Diameter and Surface Roughness Adjustment by ZIF‐8 Nanoparticles, High Wettability, Improved Mechanical Property, and Efficient Oil/Water Separation

Abstract: for oil/water separation. Among the utilized polymers, PLA has attracted much attention as a biodegradable and disposable material. [6][7][8][9] However, the oil wettability and mechanical properties of PLA electrospun membranes are not ideal, which limits its wide applications. [8,9] In addition, the diameter and roughness of the electrospun membranes also affect its separation effects. Incorporating fillers into polymer matrix is one of the effective and simple approaches to overcome the drawbacks mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 44 publications
4
36
0
Order By: Relevance
“…Moreover, another group reported that different amounts of ZIF-8 MOF nanoparticles were incorporated into the poly(lactic acid) (PLA) to prepare the nanocomposite electrospun membrane. 25 The obtained PLA/ZIF-8 electrospun nanober membranes exhibited increased oil wettability and improved mechanical property than the pure PLA membrane. It should be noted that the composite membrane with imbedded MOFs is not good at accessing external chemicals because of the polymer barrier, though these MOFs are well protected by the surrounding polymers.…”
Section: -40mentioning
confidence: 91%
“…Moreover, another group reported that different amounts of ZIF-8 MOF nanoparticles were incorporated into the poly(lactic acid) (PLA) to prepare the nanocomposite electrospun membrane. 25 The obtained PLA/ZIF-8 electrospun nanober membranes exhibited increased oil wettability and improved mechanical property than the pure PLA membrane. It should be noted that the composite membrane with imbedded MOFs is not good at accessing external chemicals because of the polymer barrier, though these MOFs are well protected by the surrounding polymers.…”
Section: -40mentioning
confidence: 91%
“…Dai et al [52] reported ZIF-8 in a PLA nanofiber matrix for oil/ water separation. The PLA/ZIF-8 nanofiber membranes showed increased oil wettability and significantly improved mechanical properties, as compared with pure PLA membranes.…”
Section: Water Treatmentmentioning
confidence: 99%
“…Mostly polymer nanofibers are produced by electrospinning but also metal, ceramic-based nanofibers have been obtained. [51][52][53][54][55] The highly open and interconnected nanofiber structure allows excellent access of fluids, e.g., low transport limitations for gases and liquids. These properties make nanofibers very interesting for a wide range of applications in energy storage and conversion, medical and healthcare, biotechnology to environmental engineering.…”
Section: Introductionmentioning
confidence: 99%
“…MOF-based mixed matrix membranes for liquid separations have been reviewed [89]. In the one study on oil/water separation that is reported, the nanoparticles of ZIF-8 have been incorporated into poly(lactic acid) or PLA to prepare an electrospun nanocomposite membrane [90]. The PLA/ZIF-8 membrane showed increased oil wettability, significantly better mechanical properties and a much higher separation efficiency than the parent PLA membrane, indicating that it could be a good candidate for oil/water separation.…”
Section: Metal-organic Framework (Mofs)/poly(lactic Acid)mentioning
confidence: 99%